Sustained attention to spontaneous thumb sensations activates brain somatosensory and other proprioceptive areas - Bauer, Clemens C.C.; Díaz, José-Luis; Concha, Luis; Barrios, Fernando A. (Brain and cognition, 2014)
The present experiment was designed to test if sustained attention directed to the spontaneous sensations of the right or left thumb in the absence of any external stimuli is able to activate corresponding somatosensory brain areas. After verifying in 34 healthy volunteers that external touch stimuli to either thumb effectively activate brain contralateral somatosensory areas, and after subtracting attention mechanisms employed in both touch and spontaneous-sensation conditions, fMRI evidence was obtained that the primary somatosensory cortex (specifically left BA 3a/3b) becomes active when an individual is required to attend to the spontaneous sensations of either thumb in the absence of external stimuli. In addition, the left superior parietal cortex, anterior cingulate gyrus, insula, motor and premotor cortex, left dorsolateral prefrontal cortex, Broca’s area, and occipital cortices were activated. Moreover, attention to spontaneous-sensations revealed an increased connectivity between BA 3a/3b, superior frontal gyrus (BA 9) and anterior cingulate cortex (BA 32), probably allowing top-down activations of primary somatosensory cortex. We conclude that specific primary somatosensory areas in conjunction with other left parieto-frontal areas are involved in processing proprioceptive and interoceptive bodily information that underlies own body-representations and that these networks and cognitive functions can be modulated by top-down attentional processes.